Motoric cognitive risk syndrome and incident hospitalization in Quebec's older population: Results of the NuAge cohort study - Beauchet, Olivier; Matskiv, Jacqueline; Launay, Cyrille P.; Gaudreau, Pierrette; Allali, Gilles (Frontiers in Medicine, 2022)
Background. Screening older adults at risk of hospitalization is essential to prevention of this adverse event. Motoric cognitive risk syndrome (MCR) has been associated with incident dementia and falls, which are both risk factors of hospitalization. There is no information on the association of MCR with incident hospitalization in older adults. Objective. The study aims to examine the association of MCR with incident hospitalization in community-dwelling older adults. Design. Quebec older population-based observational cohort study with 3 years of follow-up. Setting. Community dwellings. Subjects. A subset of 999 participants recruited in the NuAge study. Methods. Participants with MCR (i.e., with slow gait and cognitive complaint without dementia or motor disability) were identified at baseline assessment. Incident hospitalization (i.e., >1) and its recurrence (i.e., >2) were collected annually over a 3-year follow-up period. Results. The prevalence of MCR was 5.0% at baseline. The overall incidence of hospitalization was 29.0% and its recurrence 4.8%. MCR was associated with incident recurrent hospitalization (adjusted Hazard Ratio (aHR)=2.58 with 95% Confidence Interval (CI)=[1.09-6.09] and P=0.031), but not with incident hospitalization (aHR=1.48, with 95%CI=[0.95-2.28] and P=0.081). Conclusion. MCR is associated with incident recurrent hospitalization in NuAge participants, suggesting that MCR may be of clinical interest for screening individuals at risk for hospitalization in Quebec’s older population.